Incisional Wound Vacuum—Evaluation of Wound Outcomes in Comparison With Standard Dressings for Posterior Spinal Fusions in Traumatic Patients. Issue 2 (2nd February 2023) - Mehkri, Yusuf; Hernandez, Jairo; Panther, Eric; Gendreau, Julian; Pafford, Ryan; Rao, Dinesh; Fiester, Peter; Rahmathulla, Gazanfar
Abstract : BACKGROUND: Postoperative incisional negative pressure wound vacuum–assisted closure (VAC) dressings are being used as a primary dressing to optimize wound healing and help avoid complications of infection and dehiscence. Few studies have investigated whether application of VAC dressings on postoperative posterior spinal wounds can reduce the incidence of surgical site infections. OBJECTIVE: To describe our single-surgeon experience of using primary VAC after posterior spinal fusion (PSF) in a large sample of trauma patients. METHODS: This was an Institutional Review Board–approved retrospective comparative study and included all trauma patients presenting to our level 1 safety-net trauma center who required PSF and were operated on by the senior surgeon between 2016 and 2021. Primary outcomes were complications (surgical site infection, readmission for infection, and wound-related return to operating room [OR]) within 90 days after surgery. χ 2 testing and Student t testing were used to assess differences between treatment groups while bivariate and multivariate regression was performed for outcome assessment. RESULTS: Two hundred sixty-four patients met criteria and were included. One hundred fifty-seven (59%) were treated with standard dressing and 107 (41%) with VAC. Patients treated with VAC were more likely to be older ( P = .015), have diabetes ( P = .041), have an elevated body mass index ( P = .020), and had more levels of fusion ( P = .002). Despite this, presence of VAC was independently associated with decreased 90-day infection (hazard ratio = 0.397, P = .023) and decreased 90-day return to OR for wound-related reasons (hazard ratio = 0.099, P = .031). CONCLUSION: Compared with the use of standard dressing, VAC was found to decrease surgical site infection and return to OR risk in trauma patients undergoing PSF.